Characteristics of Water-Soluble Collagen Extracted from Catfish (Pangasius sp.) Skin Using Different Acetic Acid (CH3COOH) Concentrations - S.Pi., M. Si, Patmawati; Nuzil Romadhoni, Puput; Puspitaningsih , Devi; Sulmartiwi, Laksmi; Nirmala, Dwitha; Endi Rahmantyo, Lastiko; Moechthar, Oemar; Raseetha, Siva; Akmal Alwi Husein, Mohamad; Khadijah Zai (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Optimized extraction enhances fish skin-based collagen as an alternative to bovine and porcine sources. Hydro-Extraction Advantage offer a cost-effective approach for producing high-purity, water-soluble collagen. Varying CH₃COOH concentrations influence collagen yield and solubility, impacting its potential applications in food, pharmaceutical, and cosmetic industries. Hydro-extracted collagen is biodegradable and free of harmful residues. Abstract Collagen extraction from fish skin offers a sustainable approach to valorize fish processing by-products, and fish skin catfish (Pangasius sp.) is recognized as a promising collagen source. However, previous studies reported that in low water solubility, limiting its functional application in food, pharmaceutical, and cosmetic industries. To address this challenge, this study investigates the use of varying acetic acid concentrations (0.4, 0.6, and 0.8 M) during the hydrolysis stage prior to hydro-extraction, aiming to enhance the solubility and quality of the extracted collagen. Parameters measured included yield, solubility, proximate composition (protein, fat, air content, ash), organoleptic quality, molecular weight, amino acid profile and functional groups analysis. The best results were achieved with 0.6 M acetic acid, resulting in type I collagen coupled by the amide groups A, B, I, II, III, and molecular weights (65, 95, 130 and 270 kDa). The dominant amino acids identified was glycine. This treatment yielded a collagen extraction rate of 9.04% and solubility of 79.71%. The proximate composition included 67.34% protein, 14.87% fat, 8.48% moisture, and 10.69% ash. Organoleptic scores for appearance, odour, and texture were 7.80, 7.93, and 6.80, respectively. The collagen met the SNI 8076:2020 standard for protein content, moisture, and organoleptic attributes; however, fat and ash contents exceeded the specified limits. In conclusion, the acetic acid concentration significantly affects the physicochemical and sensory properties of collagen. Catfish skin shows strong potential as a raw material for collagen production, which supports its use in the food, pharmaceutical, and cosmetic sectors.